2022
DOI: 10.1097/pas.0000000000001858
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic and Molecular Study of Hybrid Nerve Sheath Tumors Reveals Their Common Association With Fusions Involving VGLL3

Abstract: A subset of benign peripheral nerve sheath tumors are "hybrid" combining several lines of differentiation, most often schwannian and perineurial features. The pathogenesis of these tumors was poorly described until the recent discovery of recurrent VGLL3 rearrangements in hybrid schwannoma/perineuriomas, supporting the hypothesis that this entity represents a distinct subgroup of tumors and not only a morphologic variation of other peripheral nerve sheath tumors. Following this finding, we investigated 10 case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…Although histologically similar to soft tissue perineurioma, such tumors are composed of two different cytotypes, namely, perineurial cells (EMA/claudin/GLUT1-positive) variably arranged into fascicular, storiform, or reticular arrangements and spindled cells (S100/SOX10-positive) with wavy nuclei, closely reminiscent of schwannian differentiation. Only rarely, hybrid tumors with both neurofibroma and perineurioma features have been reported in the literature [ 69 , 70 , 71 , 72 ]. Their classification is still to be defined, as it is not clear if they represent a “true” distinct category or simply neurofibromas rich in perineurial cells.…”
Section: Hybrid Tumorsmentioning
confidence: 99%
“…Although histologically similar to soft tissue perineurioma, such tumors are composed of two different cytotypes, namely, perineurial cells (EMA/claudin/GLUT1-positive) variably arranged into fascicular, storiform, or reticular arrangements and spindled cells (S100/SOX10-positive) with wavy nuclei, closely reminiscent of schwannian differentiation. Only rarely, hybrid tumors with both neurofibroma and perineurioma features have been reported in the literature [ 69 , 70 , 71 , 72 ]. Their classification is still to be defined, as it is not clear if they represent a “true” distinct category or simply neurofibromas rich in perineurial cells.…”
Section: Hybrid Tumorsmentioning
confidence: 99%
“…[7][8][9][10][11] Recent RNA sequencing studies have revealed a high frequency of VGLL3 fusions in hybrid schwannoma-perineurioma; the most common fusion partners include CHD7, CHD9, and MAMLD1. 12,13 Finally, VGLL4 was shown recently to play an important role in prognosis and tumorigenesis in breast and lung cancer. 14 To our knowledge only a single case of myogenic sarcoma has been recently reported to harbor a VGLL3 fusion (reported as spindle cell RMS).…”
Section: Introductionmentioning
confidence: 99%
“…Amplification of VGLL3 (mapped to chromosome 3p12) was detected in myxoinflammatory fibroblastic sarcoma (MIFS) and MIFS‐like tumors 7–11 . Recent RNA sequencing studies have revealed a high frequency of VGLL3 fusions in hybrid schwannoma‐perineurioma; the most common fusion partners include CHD7 , CHD9 , and MAMLD1 12,13 . Finally, VGLL4 was shown recently to play an important role in prognosis and tumorigenesis in breast and lung cancer 14 …”
Section: Introductionmentioning
confidence: 99%
“…Soft tissue perineuriomas harbor chromosomal losses, most commonly of chromosomes 22, 17, 2, or 6, 58 while intraneural perineuriomas often have TRAF7 mutations 59 . The much rarer hybrid nerve sheath tumors often have VGLL3 fusions instead, suggesting a different developmental pathway from simple nerve sheath tumors 60 . However, because the aforementioned molecular alterations are not pathognomonic currently the diagnosis of these benign nerve sheath tumors does not require molecular testing.…”
Section: Characteristic Genetic Alterations In Soft Tissue Tumorsmentioning
confidence: 99%
“… 59 The much rarer hybrid nerve sheath tumors often have VGLL3 fusions instead, suggesting a different developmental pathway from simple nerve sheath tumors. 60 However, because the aforementioned molecular alterations are not pathognomonic currently the diagnosis of these benign nerve sheath tumors does not require molecular testing.…”
Section: Characteristic Genetic Alterations In Soft Tissue Tumorsmentioning
confidence: 99%